1975
DOI: 10.1093/infdis/131.5.579
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Human in Vivo and in Vitro Cutaneous Antimicrobial Factors

Abstract: the presence of antimicrobial substances on human skin was investigated. Staphyloccus aureus (10-4 colony-forming units) was applied on the forearm of 50 subjects and covered with a semiocclusive device for 24 hr. In 54% of the subjects the organisms persisted, and in 34% S. aureus was inhibited on the skin. Subjects with persistent S. aureus also had persistent Candida albicans, and vice persa. This correlation was not noted with Streptococcus pyogenes. Skin lipids from the two groups of subjects were extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
2

Year Published

1980
1980
2011
2011

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(28 citation statements)
references
References 7 publications
1
25
0
2
Order By: Relevance
“…When skin surface acetone extracts were replaced on washed skin, the increased bacterial counts were not seen. Aly et al (34,35) also demonstrated a direct correlation between the degree of killing of experimentally applied staphylococci, streptococci, and candida and degree of inhibition in vitro by acetone extracts of the skin surface. It has been suggested that FFA can affect the flora of the gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…When skin surface acetone extracts were replaced on washed skin, the increased bacterial counts were not seen. Aly et al (34,35) also demonstrated a direct correlation between the degree of killing of experimentally applied staphylococci, streptococci, and candida and degree of inhibition in vitro by acetone extracts of the skin surface. It has been suggested that FFA can affect the flora of the gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 95%
“…Fatty acids are well-known antimicrobial substances with activity in vitro against gram-positive and gram-negative bacteria (22)(23)(24)(25)(26), fungi (27,28), and enveloped viruses, including influenza (29)(30)(31) (34,35) showed that staphylococci, streptococci, and candida rapidly decreased in number after being deposited on normal skin, whereas acetone-washed skin allowed greater persistence of the microorganisms. When skin surface acetone extracts were replaced on washed skin, the increased bacterial counts were not seen.…”
Section: Discussionmentioning
confidence: 99%
“…An acidic SC is believed to provide an antimicrobial function, with inhibition of growth of pathogenic bacteria. 15,16,32 The acid mantle may facilitate colonization of the skin surface with commensal organisms. 30,33 Additional studies are warranted to assess the impact of vernix retention on the process of skin colonization.…”
Section: Skin Surface Adaptation and Acid Mantle Developmentmentioning
confidence: 99%
“…An acid surface is putatively necessary for the bacterial homeostasis/colonization of the skin. 15,16 Finally, birth marks a time of high oxidative stress. Adult human skin possesses endogenous antioxidant capacity in the form of alpha tocopherol (vitamin E) localized in SC and in sebum.…”
Section: Introductionmentioning
confidence: 99%
“…Lipids have been reported to have antimicrobial function in human milk [143][144][145][146][147][148][149][150], lung surfactant [151,152], skin [153], and a number of marine algae [154,155]. Lipases present in human milk (lipoprotein lipase and bile salt activated lipase) hydrolyze milk triglyceride during storage at 4-38°C [156], contributing to a rise in free fatty acid levels that might contribute to resistance to bacterial growth [156].…”
Section: Lipidsmentioning
confidence: 99%